Biological Activities of Grape Seed By-Products and Their Potential Use as Natural Sources of Food Additives in the Production of Balady Bread - Haiam O. Elkatry; Abdelrahman R. Ahmed; Hossam S. El-Beltagi; Heba I. Mohamed; Nareman S. Eshak (Foods, 2022)
The biological function of bioactive compounds found in plant by-products has triggered expanded interest in recent years. This study aims to produce balady bread enriched with dietary fiber, mineral, and phenolic compounds by the addition of grape seeds powder (GSP) at different levels (5%, 10%, and 15% as a partial substitute for wheat flour). The results show that balady bread (Bb) and grape seed powder have ash contents of about 1.97% and 3.04%, lipid contents of 3.22% and 17.15%, protein contents of 11.16% and 12.10%, fiber contents of 1.06% and 44.90%, and carbohydrates contents of 56.52% and 29%, respectively. Moreover, grape seed powder contains a higher level of iron and zinc about 30.02 and 9.43 mg/kg than the Bb control sample which contains about 8.19 and 7.25 mg/kg respectively. The findings revealed that balady bread fortified with grape seed powder contains a high amount of total polyphenols content (TPC), total flavonoid content (TF), and antioxidant capacity. The farinograph test results showed that increasing the GSP concentration in the flour above 10% reduced dough development, stability, and farinograph quality number. The addition of GSP to wheat flour accelerated the dough’s water absorption and mixing tolerance. Grape seed incorporation levels up to 10% (w/w) had no negative effect on dough rheological performance. The sensory evaluation of bread showed that samples that were enriched with grape seeds powder at up to 10% had good quality. Based on these findings, it is recommended to replace up to 10% GSP in the manufacturing of fortified balady bread with satisfactory physical and sensory characteristics and high TPC and antioxidant activity.